Envelope-constrained filter design : an LMI approach - Tan, Zhiqiang (2008)
This thesis examines the design of discrete-time envelope-constrained (EC) filters including EC filters with uncertain input, and EC deconvolution filters. Our solutions are based on linear matrix inequality (LMI) approaches.